Bioactive Chemical Compounds Identified in Extracts of Reseda sphenocleoides Leaves and Evaluation of Antiamoebic Activity In Vitro - H. Mehdi, Mansour A.; Mohsin, Mohammad; Alarabi, Fadel Y.S.; Omar, Gozif Mohammed N.; Farooqui, Mazahar; Pradhan, Vidya (Anti-Infective Agents, 2021)
Background: Entamoeba histolytica is a causative agent of amoebiasis, estimated to cause more than 100,000 deaths per year. Metronidazole is used to treatment of E. histolytica infection. However, this drug has several untoward side effects, the current study was designed to analysis of the bioactive chemical products in extracts of Reseda sphenocleoides leaves and evaluation of anti-amoebic activity in vitro. Methods: Bioactive chemical compounds were tested by GC-MS and FT-IR. Entamoeba histolytica was cultured under xenic conditions in Locke's egg (LE) medium and different concentrations of extracts of R. sphenocleoides were added to cultivated parasites. Results: 11 and 18 bioactive phytochemical compounds were shown in the ethanolic and aqueous extracts of R. sphenocleoides leaves, respectively, by GC-MS analysis. FT-IR analysis of extracts of R. sphenocleoides leaves proved the presence of many functional groups for various phytocompounds. The ethanolic extract of R. sphenocleoides leaves was inhibited the growth of E. histolytica in vitro at concentrations 5 and 10 mg/ml after 96 hrs of incubation. At the same time, the highest concentration 20 mg/ml used in this study, inhibited the E. histolytica at all times of incubation. The aqueous extract showed that there was no growth of E. histolytica at the concentrations of 5 and 10 mg/ml after 72 and 48 hrs, respectively. However, the higher concentrations (15 and 20 mg/ml) of the aqueous extract were on the growth of E. histolytica parasite during the period of incubation. It was found that the minimum inhibitory concentration (MIC) for ethanolic and aqueous extracts of R. sphenocleoides leaves was <15 mg/ml and <10 mg/ml, respectively. Conclusion: The results specify that the extracts of R. sphenocleoides has a higher capacity of reducing E. histolytica number in vitro. Moreover, these results showed that the extracts of R. sphenocleoides contain various bioactive compounds and therefore have various medicinal properties that can be used for the treatment of various diseases.
Keywords: in vitro